Influence of Career Development and Organizational Culture on Employee Performance in Nepalese Insurance Companies - Mathema, Laxmi Bir; Bist, Diwakar (Nepalese Journal of Management, 2024)
The study examines the influence of career development and organizational culture on employee performance in Nepalese insurance companies. Employee performance is selected as the dependent variable. The selected independent variables are management support, mentors, supportive organizational culture, employee training, reward system, and promotion. The study is based on primary data with 106 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and impact of career development and organizational culture on employee performance in Nepalese insurance companies. The study showed that management support has a positive impact on employee performance. It indicates that higher the management support, higher would be the employee performance. Similarly, support of mentors has a positive impact on employee performance. It indicates that supportive mentors lead to increase in employee performance. Likewise, supportive organizational culture has a positive impact on employee performance. It indicates that supportive organizational culture leads to increase in employee performance. Further, reward system has a positive impact on employee performance. It indicates that fairness in reward system leads to increase in employee performance. In addition, employee training has a positive impact on employee performance. It indicates that increase in employee training leads to increase in level of employee performance. Moreover, promotion has a positive impact on employee performance. It indicates that fair and timely promotion leads to increase in employee performance.